SELECTIVENESS OF THE EXPOSURE-BASED PERCEPTUAL LEARNING: WHAT TO LEARN AND WHAT NOT TO LEARN - Choi, Hoon (2009)
How does the brain determine what to learn and what not to learn? Previous studies showed that a feature or stimulus on which subjects performed a task was learned, while the features or stimuli that were irrelevant to the task were not learned. This led some researchers to conclude that attention to a stimulus was necessary for the stimulus to be learned. This thought was challenged by the discovery of a task-irrelevant perceptual learning, in which learning occurred by mere exposure to the unattended and subthreshold stimulus. However, this exposure-based learning does not necessarily indicate that all presented stimuli are learned. Rather, recent studies showed that the occurrence of this learning was very selective for the following new findings: unattended stimulus learning occurred only (1) when the unattended stimulus was associated temporally with the processing of an attended target, (2) when the unattended stimulus was synchronously presented with reinforcers, such as internal or external rewards, and (3) when the unattended stimulus had subliminal properties. These selectivities suggest some degrees of similarity between task-relevant and task-irrelevant perceptual learning, which has been the motivation for making a united model in which both task-relevant and task-irrelevant learning are formed with similar or same mechanisms.